Following the Balkan Migration Route: Informal Spatial Practices Created by "People on the Move" - Žarković, Tatjana; Jocić, Nikola (Technium Social Sciences Journal, 2021)
Informal migrations from the Middle East and North Africa to Europe since 2015 and their social, economic, and political implications have attracted the attention of the general public and policymakers, but have also been the focus of research in numerous social and urban studies. As a region in the transitional phase, and officially in the process of EU accession, the Western Balkan countries offer a special perspective. In that sense, Serbia, as well as Bosnia and Herzegovina (BiH), play important roles as countries that border the EU, and therefore suitable ground for the analysis of the practices of setting boundaries, actual state of porosity of boundaries set, both symbolic and physically at the local and global level. An increasing number of migrants has developed various informal spatial practices, as well as initiated changes in public spaces. The new dynamics emphasize these spaces’ characteristics as those of public and collective participation, as well as of potential conflicts, and permanent transformation processes. On the one hand, massive migration flows have triggered increased nationalism, xenophobia, and fear, but have also increased civic engagement and led to new solidarities, not only ‘from above’, but also ‘from bellow’. This article examines public spaces beyond a neoliberal discourse by highlighting their function as meeting points, offering possibilities for dialog between ‘privileged’ and ‘unprivileged’ population.